FOXP3+ Treg Cells and Gender Bias in Autoimmune Diseases - Nie, Jia; Li, Yang Yang; Zheng, Song Guo; Tsun, Andy; Li, Bin (Frontiers in Immunology, 2015)
CD4+CD25+ Regulatory T (Treg) cells play a pivotal role in the maintenance of immune homeostasis, where the X-linked master transcription factor Forkhead box P3 (FOXP3) determines Treg cell development and function. Genetic deficiency of Foxp3 induces dysfunction of Treg cells and immuno-dysregulation, polyendocrinopathy, enteropathy X (IPEX)-linked syndrome in humans. Functionally deficient Treg cells or the development of exTreg cells positively correlate with autoimmune diseases such as systemic lupus erythematosus (SLE), multiple sclerosis (MS) and ankylosing spondylitis (AS). In general, females are more susceptible to SLE and MS but less susceptible to AS, where the expression of FOXP3 and its protein complex are perturbed by multiple factors including hormonal fluctuations, inflammatory cytokines and danger signals. Therefore, it is critical to explore the potential molecular mechanisms involved and these differences linked to gender. Here we review recent findings on the regulation of FOXP3 activity in Treg cells and also discuss gender difference in the determination of Treg cell function in autoimmune diseases.